1966
DOI: 10.1136/jcp.19.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels in normal pregnancy with observations on the renal excretion of urate in pregnancy

Abstract: SYNOPSIS Serum uric acid estimations were performed in 106 healthy pregnant women during early, middle, and late pregnancy, using an automated colorimetric method. The mean serum uric acid level was significantly lower during early and middle pregnancy than that of 64 age-matched female controls. The serum uric acid level was not significantly different in late pregnancy from the control group. Studies of the daily urinary urate excretion in 31 pregnant women showed normal urinary urate excretion in early preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
2

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 3 publications
1
27
2
2
Order By: Relevance
“…However, it is likely that alterations in both GFR and tubular reabsorption would be needed to account for the magnitude of some of the excretion rates noted. Finally, serum uric acid has been documented to be decreased in the first trimester, nadir in the second trimester, and then gradually increase as pregnancy progresses and high renal clearance is thought to be necessary to clear the increased production that accompanies fetal and/or placental growth (60,61). As such, uric acid has been noted to be elevated in pregnancies complicated by pre-eclampsia (62) and is often used to assist with the diagnosis of preeclampsia.…”
Section: Tubular Functionmentioning
confidence: 99%
“…However, it is likely that alterations in both GFR and tubular reabsorption would be needed to account for the magnitude of some of the excretion rates noted. Finally, serum uric acid has been documented to be decreased in the first trimester, nadir in the second trimester, and then gradually increase as pregnancy progresses and high renal clearance is thought to be necessary to clear the increased production that accompanies fetal and/or placental growth (60,61). As such, uric acid has been noted to be elevated in pregnancies complicated by pre-eclampsia (62) and is often used to assist with the diagnosis of preeclampsia.…”
Section: Tubular Functionmentioning
confidence: 99%
“…Serum uric acid levels have been reported to be significantly lower during early and middle pregnancy, as compared to age-matched female controls (Boyle, et al, 1966). Laughon et al (2008) from the US found that hyperuricemia was a dose-dependent risk factor for the development of Gestational diabetes mellitus (GDM) amongst pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal serum uric acid levels decrease by 25–35% during the first trimester due to an increase in glomerular filtration rate and a decrease in reabsorption in the proximal tubule. There is a subsequent rise to prepregnancy levels near term, which is related to a decrease in uric acid clearance due to postsecretory reabsorption [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%